Laparoscopic retrieval of a foreign body (broken surgical knife) from retroperitoneal space: An interesting case - Dipak Limbachia; Preeti Gandhi (Wolters Kluwer Medknow Publications, 2017)
We present a rare and interesting case, of a retrieval of a broken surgical knife blade, from the retroperitoneal space, through laparoscopic approach by a gynecology endoscopist. A 40-year-old man underwent open lumbar discectomy surgery, when the surgical knife blade inadvertently broke, and was retained in the disc space. The broken blade could not be removed during the initial surgery. A second attempt was made to retrieve it; however, it migrated further anteriorly into the retroperitoneal space. Subsequently, a gynecology endoscopist was called in, who successfully retrieved the broken blade from the retroperitoneal space through laparoscopic approach. A four-port laparoscopic transperitoneal approach was performed. The broken fragment of the knife was found just medial to the left common iliac artery in the retroperitoneal space, which was removed. Operation time was 40 minutes and the postoperative course was uneventful. Keywords: broken knife, foreign body, laparoscopy, retroperitoneal